Beautiful flesh: a body of essays - Stephanie G'Schwind, editor; The Center for Literary Publishing, Colorado State University, publisher (Colorado State University. Libraries, 2017)
Selected from among the country's leading literary publications--Colorado Review, Crazyhorse, Creative Nonfiction, the Georgia Review, the Normal School, Prairie Schooner, and others--Beautiful Flesh gathers nineteen works of creative nonfiction to build a multi-gender, multi-ethnic body out of essays, each concerning a different part of the body: belly, blood, bones, brain, ears, eyes, feet, hair, hands, heart, knees, lungs, nose, ovaries, pancreas, sinuses, skin, spine, teeth, and vas deferens. The title is drawn from Wendy Call's contribution, "Beautiful Flesh," a meditation on the pancreas: "gorgeously ugly, hideously beautiful: crimson globes embedded in a pinkish-tan oval, all nestled on a bed of cabbage-olive green, spun through with gossamer gold." Other essays include Dinty W. Moore's "The Aquatic Ape," an exploration of the curious design and necessity of sinuses; Katherine E. Standefer's "Shock to the Heart, Or: A Primer on the Practical Applications of Electricity," a modular essay on the author's internal cardiac defibrillator and the nature of electricity; Matt Roberts's "Vasectomy Instruction No. 7," which considers the various reasons for and implications of surgically severing and sealing the vas deferens; Lupe Linares's "A Living Structure," concerning teeth and the "small mistakes that accumulate over time and add up to a loss that we can never forget"; and Peggy Shinner's "Elective," which examines the author's own experience with rhinoplasty and cultural considerations of the "Jewish nose." Echoing the myriad shapes, sizes, abilities, and types of the human body, these essays showcase the many forms of the genre--provided by publisher.
Field notes on hair / Vicki Weiqi Yang -- Gray area: thinking with a damaged brain / Floyd Skloot -- The aquatic ape hypothesis, or how I learned to love my paranasal sinuses / Dinty W. Moore -- Looking back / Danielle R. Spencer -- Elective / Peggy Shinner -- Speaking of ears and savagery / Steven Church -- A living structure / Lupe Linares -- The spine / Sarah Rose Etter -- Drawing a breath / Kaity Teer -- Shock to the heart, or: a primer on the practical applications of electricity / Katherine E. Standefer -- Blood type / Samantha Simpson -- Mos teutonicus / Matthew Ferrence -- Wolf biter / Sarah Viren -- The private life of skin / Hester Kaplan -- Beautiful flesh / Wendy Call -- The belly of desire / Sarah K. Lenz -- The population of me / Jody Mace -- Pre-vasectomy instruction no. 7 / Matt Roberts -- Taking shape / Amy Butcher -- Once, then / Angela Pelster
Keywords: American essays -- 21st century; Human body in literature